Agunan KUR Tanpa Agunan: Inkonsistensi Regulasi dan Jalan Menuju Penjaminan Hybrid - Leny Megawati; T Subaryah; Tuti Rastuti (Jurnal Penelitian Hukum De Jure, 2025)
This study was motivated by the discrepancy between the norm stating that People’s Business Credit (KUR) with a ceiling of up to IDR100 million does not require additional collateral, and the operational policy that still requires collateral at a number of Bank BRI units. This discrepancy causes disharmony and inconsistency, which has the potential to lead to disputes and hinder access to financing for MSMEs. The approach used is socio-legal research that combines normative-legal and socio-empirical research techniques. Based on these findings, this study examines the implications of applying additional collateral in the People’s Business Credit (KUR) program at Bank BRI, particularly for micro-entrepreneurs with limited assets, where consumer protection norms and fairness in banking relationships do not explicitly accommodate credit insurance as a valid and standardized alternative guarantee, resulting in excessive dependence on physical collateral such as land, buildings, or vehicles, which actually hinders access to credit for MSMEs with minimal asset structures and creates discriminatory risks and legal uncertainty in the financing distribution process, threatening the consistency of the principles of fairness and openness that form the legal basis for consumer-bank relationships.